Respiration and circulation - Spilsbury, Louise (Heinemann Library, 2008)
Discusses the structure and functions of the respiratory and circulatory systems, and explains breathing, the composition of blood, how energy is obtained and used, and how to keep the heart and lungs healthy, and includes a glossary and color illustrations.